MONOLITH WEB-SERVICES AND MICROSERVICES: COMPARATION AND SELECTION - Руслан Григорьевич Клапчук; Вячеслав Сергеевич Харченко (Радіоелектронні і комп'ютерні системи, 2017)
The paper is dedicated to analysis of two most commonly used architectures for creation of web services– monolith and microservice. Relevance of the subject is caused by the continuous growth of web resources users and the need of service scaling. The common notions related to the subject is defined, the main properties of web services are analyzed, monolith and microservice architectures are compared. Besides, the article contains recommendations regarding choice of the most suitable architecture for the very web resource